Multi-scale hybrid eco-nanocomposites: synthesis and characterization of nano-SiC-reinforced vinyl-ester eco-composites - Alhuthali, A.; Low, It Meng (Springer, 2013)
Polymer eco-nanocomposites based on vinyl-ester, recycled cellulose fibre and nano-silicon carbide (n-SiC) have been synthesized and characterized in terms of porosity, water-absorption behaviour, thermal and mechanical properties. The addition of n-SiC led to reduced porosity and water uptake because of enhanced fibre–matrix adhesion which permitted efficient load transfer and thus strength improvement. However, n-SiC addition reduced the prevalence of fibre debonding and pull-outs, thus causing sample brittleness and inferior fracture toughness. In terms of thermal properties, n-SiC addition facilitated improved mass transport and heat barriers, thus improving thermal stability and fire resistance.